2017
DOI: 10.2175/106143017x14839994523028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing UV Inactivation of Adenovirus 41 Using Integrated Cell Culture Real‐Time qPCR/RT‐qPCR

Abstract: Enteric adenoviruses are among most UV-resistant viruses in water. Cytopathic effects (CPE)-based cell culture TCID50 assay as a conventional virus assessment approach has major drawbacks for enteric adenovirus since it is selective on cell lines and takes longer time to show CPE. Integrated cell culture real-time quantitative PCR (ICC-qPCR) and reverse transcriptase (RT)-qPCR were applied in this study, in comparison with TCID50, to assess UV inactivation of adenovirus type 41 (Ad41) in water. Adenovirus type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These disadvantages, inherent to the method, present critical barriers in assessing the efficacy of disinfection applications against human enteric viruses. To overcome some of these hurdles, tissue/cell culture based methods have been integrated with rapid molecularbased detection methods and have been successfully applied in disinfection studies of human adenoviruses and enteroviruses (Ding et al, 2017;Gerrity et al, 2008;Ko et al, 2005;Rodriguez et al, 2013;Ryu et al, 2015). Of particular interest, Mayer et al (2010) reported the simultaneous quantification of two serotypes of Enterovirus B (coxsackievirus B6 and echovirus 12) and one serotype of Enterovirus C (poliovirus 1) using a singular tissue culture line with three serotype specific reverse transcriptase quantitative PCR (RTqPCR) assays.…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages, inherent to the method, present critical barriers in assessing the efficacy of disinfection applications against human enteric viruses. To overcome some of these hurdles, tissue/cell culture based methods have been integrated with rapid molecularbased detection methods and have been successfully applied in disinfection studies of human adenoviruses and enteroviruses (Ding et al, 2017;Gerrity et al, 2008;Ko et al, 2005;Rodriguez et al, 2013;Ryu et al, 2015). Of particular interest, Mayer et al (2010) reported the simultaneous quantification of two serotypes of Enterovirus B (coxsackievirus B6 and echovirus 12) and one serotype of Enterovirus C (poliovirus 1) using a singular tissue culture line with three serotype specific reverse transcriptase quantitative PCR (RTqPCR) assays.…”
Section: Introductionmentioning
confidence: 99%
“…(A) Standard linear regression models for LP-UV inactivation of adenovirus 2 ,,,, + 5 , + 15 (not significantly different), AdV40, and AdV41. ,, Blue squares, orange triangles, and gray diamonds represent extracted data, while linear regressions are described with blue, orange, and gray lines for AdV2 + 5, 40, and 41, respectively. The 95% confidence interval is indicated by the shaded area.…”
Section: Resultsmentioning
confidence: 99%
“…Damage to different components of viruses caused by varying wavelengths has implications for the accuracy of detection methods. Molecular methods are a convenient proposition for enteric virus detection because infectivity assays for quantification are highly dependent on cell lines and can take days to weeks to produce cytopathic effects (CPEs). ,, Long-range qPCR (LR-qPCR) has been previously used for viral quantification after UV damage ,, and has been shown to give similar results for infectivity-based methods when using LP-UV . While molecular methods are sensitive and precise, they are only effective in detecting damage to their specific molecular target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations